BUSINESS FEASIBILITY STUDY OF SCOOP AND CHILL GELATO BAR IN SOUTH JAKARTA - Marcella, Jennifer; Wowor, Wulanmeiaya (IJOSMAS, 2023)
The purpose of this study was to look into the feasibility of Scoop and Chill Gelato Bar as a new business in South Jakarta. Scoop and Chill Gelato Bar is an ice cream shop that sells vegan gelato as the main product due the increasing of health awareness and maintaining a healthy lifestyle after the pandemic of COVID – 19. .This study is driven by the growth of food and beverages industry in 2022 post pandemic. Primary data is gathered using questionnaire filled by 152 respondents and secondary data gathered from external sources. To measures the feasibility of Scoop and Chill Gelato Bar, there are some aspects such as financial, human resources, marketing and operational aspect. The financial use feasibility of investment such as Break-even Point (BEP), Net Profit Value (NPV), Payback Period (PP). The analysis of financial shows Scoop and Chill Gelato Bar is feasible to operate with minimum break-even point value of Rp3,638,574,382 per year and 2 year, 4 months and 25 days to achieve payback period. The financial also shows the Net Present Value is Rp9,676,607,483 (NPV>0). The analysis shows that Scoop and Chill Gelato Bar is profitable and feasible to operate. Keywords – Feasibility Study, Vegan, Gelato, South Jakarta.